From p‐ to n‐Type Mixed Conduction in Isoindigo‐Based Polymers through Molecular Design. Issue 14 (23rd February 2022) - Parr, Zachary S.; Borges‐González, Jorge; Rashid, Reem B.; Thorley, Karl J.; Meli, Dilara; Paulsen, Bryan D.; Strzalka, Joseph; Rivnay, Jonathan; Nielsen, Christian B.
Abstract: Organic mixed ionic and electronic conductors are of significant interest for bioelectronic applications. Here, three different isoindigoid building blocks are used to obtain polymeric mixed conductors with vastly different structural and electronic properties which can be further fine‐tuned through the choice of comonomer unit. This work shows how careful design of the isoindigoid scaffold can afford highly planar polymer structures with high degrees of electronic delocalization, while subtle structural modifications can control the dominant charge carrier (hole or electron) when probed in organic electrochemical transistors. A combination of experimental and computational techniques is employed to probe electrochemical, structural, and mixed ionic and electronic properties of the polymer series which in turn allows the derivation of important structure–property relations for this promising class of materials in the context of organic bioelectronics. Ultimately, these findings are used to outline robust molecular‐design strategies for isoindigo‐based mixed conductors that can support efficient p‐type, n‐type, and ambipolar transistor operation in an aqueous environment. Abstract : A new molecular design criteria for isoindigo‐based semiconducting polymers is presented and their versatility is showcased for the development of mixed conductors relevant to organic bioelectronic applications. Through rational choice of the isoindigoid motif and an appropriate comonomer, efficient hole‐ and electron‐transport materials are developed and strategies for further optimization are identified, including the development of ambipolar mixed conductors.